Best practice principles on developing LGBT cultural competence in health and social care education - Keogh, Brian; Higgins, Agnes (Being Me Project Team, 2019)
The BEING ME project aims to support the social inclusion of Lesbian, Gay, Bisexual and Transgender (LGBT) older people who use care and wellbeing services. As the population of Europe is ageing, more and more older people are in need of care and support. This will include older LGBT people, who often need more professional care and support as many may not have children or the traditional support networks of the general population. Research has demonstrated that older LGBT people experience social exclusion while interacting with care providers and that their life stories and relationships are overlooked and undervalued. In some cases, they experience direct discrimination within health and social care environments.Research also indicates an absence of focus on older LGBT people’s health care needs within curricula content and academic textbooks, which results in health and social care providers being constrained in their ability to provide a culturally-sensitive and acceptable service to LGBT older people. There is also evidence that many educators lack the knowledge and skills to develop curricula that addresses, in an inclusive and affirmative manner,the health and social care needs of older LGBT people.The BEING ME project endeavours to achieve this aim through positive interaction with educational institutions that prepare professionals to work with older people. By exchanging good practices, including good practice in teaching and learning and by developing tailored educational resources and pedagogies, the BEING ME team aim to improve the knowledge and competencies of future care professionals in the area of LGBT affirmative practices for older people. By enhancing skills, knowledge and competencies, practitioners will be in a position to develop a culture of support, openness and respect for LGBT identities, which is essential to older LGBT people's inclusiveness in care environments.
PUBLISHED
Keywords: Social inclusion; LGBT; Older people; Care providers; Social exclusion